People and plant entanglements at the dawn of agricultural practice in Greece: an analysis of the Mesolithic and early Neolithic archaeobotanical remains - Kotzamani, Georgia; Livarda, Alexandra (Elsevier, 2018)
Investigation of the incipience of agriculture in Greece employing archaeobotanical remains is a challenging field of inquiry, aiming at gaining insights into the complex socio-economic transformations that gradually shaped the way of Neolithic life. Yet, primary archaeobotanical evidence dating to the 7th and early 6th millennium BCE from Greece still remains scarce and, to a certain degree, incomplete as regards the kind of information it can provide. This paper forms anew an approach to explore aspects of early agricultural practices in Greece on the basis of plant macroremains. The aim is to set the Mesolithic background against which the Early Neolithic archaeobotanical dataset is then fully reviewed. In doing so we first introduce new Mesolithic and early Neolithic data (Theopetra in Thessaly, and Revenia and Paliambela in Macedonia) and we then provide a critical overview of all other sites in Greece dated to these periods, to ultimately set new 'seeds' for future research on the incipience of agriculture in the area.